Clinical and Demographic Patterns of Pulmonary Tuberculosis in Patients with Diabetes Mellitus: Impact of Diabetes Mellitus on Patient - Yagnang K. Vyas; A. T. Leuva MD (Sudan Journal of Medical Sciences, 2023)
Abstract Background: Tuberculosis (TB) is a communicable infectious disease and one of the leading causes of death. Until the coronavirus pandemic, tuberculosis was the leading cause of death from a single infectious agent, more than HIV/AIDS. Due to urbanization and rapid social and economic development, there is a rapidly increasing diabetes mellitus (DM) epidemic and India has the second largest number of DM patients in the world. There are around 74.2 million DM cases and 40.1 million people with impaired glucose tolerance. Tuberculosis is more common in low- and middle-income countries. The increasing trend of the two diseases poses a major challenge for the tuberculosis control program. Methods: The main goal of this research was to investigate clinical and demographic patterns of pulmonary tuberculosis in patients with DM. It is a prospective, observational, in-hospital study. We studied 165 PTB patients associated with DM who were at least scanty/1+ positive on smear or had Mycobacterium TB sputum CBNAAT detected. Results: Of the 165 patients, 127 PTB-DM patients were male and 38 were female. The most common symptom was cough, which occurred in 164 (99.4%) patients. Fever was the second most common symptom in 152 (92.1%) patients and anorexia was the third most common symptom, occurring in 119 (72.1%) patients. Conclusion: The majority of patients were from IPD 88 (54%), suggesting that PTB–DM cases have a more severe and complicated presentation. Male patients are affected more frequently than female patients. People in the age group 31–60 years often suffer from PTB–DM. Cough, fever, and anorexia are the most common symptoms, while chest pain and breathlessness are more common in the older age group. History of PTB in DM patients is also of concern as the present study shows that there is a possible association with relapse or reactivation of PTB as well as drug resistance of PTB.